Realising birth intentions in European comparison - Understanding the post-communist fertility transition - Zsolt Sped́er; Balaźs Kapitańy (Hungarian Demographic Research Institute, 2012)
This paper strives to broaden understanding of fertility transition in post-Communist countries, starting in the early 1990s. The integration of findings from distinct avenues of fertility research and incorporation of results of an empirical analysis of new kinds into the approaches of post-Communist fertility transition leads us to new conclusions. The use of longitudinal panel studies in comparing fertility intentions and realisation in four European countries reveals the very low level of realisation of fertility intentions in post-Communist countries. We find that the distinct manner and pace of social change, the discrepancy between very slow changes in values and very rapid institutional and structural changes, are primarily responsible for the larger gap between intention and realisation in the post-Communist countries, although some compositional effects are not negligible. This understanding could be seen as an extension of the anomie approach to post-Communist transition. The contrast between macro-level postponement and individual action allows us to highlight specific causation during the post-Communist fertility transition: macro-level postponement of fertility seems at least partly to be a result of failure to realise child-bearing intentions.
Keywords: J13; 300; fertility; fertility intention; post-communist fertility transition; postponement; longitudinal study in fertility; Internationale Migration; Wanderungsstatistik; Geschichte; Südosteuropa